Base‐Free Non‐Noble‐Metal‐Catalyzed Hydrogen Generation from Formic Acid: Scope and Mechanistic Insights - Mellmann, Dörthe; Barsch, Enrico; Bauer, Matthias; Grabow, Kathleen; Boddien, Albert; Kammer, Anja; Sponholz, Peter; Bentrup, Ursula; Jackstell, Ralf; Junge, Henrik; Laurenczy, Gábor; Ludwig, Ralf; et al. (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

The Electronic Ground State of [Fe(CO)3(NO)]−: A Spectroscopic and Theoretical Study - Klein, Johannes E. M. N.; Miehlich, Burkhard; Holzwarth, Michael S.; Bauer, Matthias; Milek, Magdalena; Khusniyarov, Marat M.; Knizia, Gerald; Werner, Hans-Joachim; Plietker, Bernd (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

A series of amide functionalized isoreticular metal organic frameworks - Keceli, E.; Hemgesberg, M.; Grünker, R.; Bon, V.; Wilhelm, C.; Philippi, T.; Schoch, Roland; Sun, Y.; Bauer, Matthias; Ernst, S.; Kaskel, S.; Thiel, Werner R. (Microporous and Mesoporous Materials)
Keywords: Mechanics of Materials; Condensed Matter Physics; General Materials Science; General Chemistry

A Catalytic System for the Activation of Diorganozinc Reagents - Werner, Thomas; Bauer, Matthias; Riahi, Abdol Majid; Schramm, Heiko (European Journal of Organic Chemistry)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Polynuclear Iron(II)–Aminotriazole Spincrossover Complexes (Polymers) In Solution - Bräunlich, Irene; Sánchez-Ferrer, Antoni; Bauer, Matthias; Schepper, Rahel; Knüsel, Philippe; Dshemuchadse, Julia; Mezzenga, Raffaele; Caseri, Walter (Inorganic Chemistry)
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

HERFD-XAS and valence-to-core-XES: new tools to push the limits in research with hard X-rays? - Bauer, Matthias (Phys. Chem. Chem. Phys.)
This perspective accounts for the benefits of the high resolution hard X-ray spectroscopic methods HERFD-XANES and valence-to-core-XES.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Praxisorientiertes Projektlernen am Beispiel der Leuphana College-Studien in der Praxis. - Hellmann, Karina; Teigeler, Mareike; Seifert, Andreas (Zeitschrift für Hochschulentwicklung)

Untersuchung individueller und systemischer Wirkfaktoren auf die Rechenfertigkeit von Erstklässlern. - Eilerts, Katja; Seifert, Andreas; Rinkens, Hans-Dieter (Beiträge zum Mathematikunterricht 2014)

Understanding loyalty program effectiveness: managing target and bystander effects - Steinhoff, Lena; Palmatier, Robert W. (Journal of the Academy of Marketing Science)
Keywords: Marketing; Economics and Econometrics; Business and International Management

What we mean when we talk about freedom – The KOMFOR study: an analysis of students' choices of courses in interdisciplinary parts of the curriculum. - Seifert, Andreas; Strunz, Cathleen; Gunkel, Marjaana; Schütz, Julia (INTED2014 Conference Proceedings: 8th International Technology, Education and Development Conference March 10th-12th, 2014 – Valencia, Spain)

Alkohol, Musik und Nervenkunst – Zur Berliner Bohème des ‚Schwarzen Ferkels‘ (1892-1894) - Heidgen, Michael; Nier, Svenja (Realitätsflucht und Erkenntnissucht: Alkohol und Literatur)

Der Test zur Messung bildungswissenschaftlichen Wissens (BwW) als Beispiel der handlungsorientierten Operationalisierung kognitiver Fähigkeiten. - Seifert, Andreas (11. Sommerschule der Fakultät für Erziehungswissenschaft der Universität Hamburg.)

Wahlfreiheit am Lernort Hochschule – Die KOMFOR-Studie: Zum Wahlverhalten in fachübergreifenden Studienangeboten. - Seifert, Andreas; Schütz, Julia (DGHD-Tagung „Leitkonzepte der Hochschuldidaktik: Theorie – Praxis – Empirie")

Freiheit, die ich meine: Zum Wahlverhalten in fachübergreifenden Studienangeboten – Nomothetische und ideographische Zugänge. - Schütz, Julia; Seifert, Andreas (AEPF-Tagung „Der Forschung / Der Lehre / Der Bildung”)

Konzeptionen der Kompetenz und Möglichkeiten der Operationalisierung. - Seifert, Andreas (11. Sommerschule der Fakultät für Erziehungswissenschaft der Universität Hamburg.)

Freiheit, die ich meine: Zum Wahlverhalten in fachübergreifenden Studienangeboten – Beispiel Leuphana College. - Beck, Karin; Seifert, Andreas (Tag der Lehre an der Universität Paderborn)

Kompetenz: ein schillernder Begriff. - Seifert, Andreas (Fortbildungstag für Berufsberater_innen: „Studienziel: Employability”)

Co-development of manner and path concepts in language, action, and eye-gaze behavior - Lohan, Katrin S.; Griffiths, Sascha; Sciutti, Alessandra; Partmann, Tim C.; Rohlfing, Katharina (Topics in Cognitive Science)
In order for artificial intelligent systems to interact naturally with human users, they need to be able to learn from human instructions when actions should be imitated. Human tutoring will typically consist of action demonstrations accompanied by speech. In the following, the characteristics of human tutoring during action demonstration will be examined. A special focus will be put on the distinction between two kinds of motion events: path-oriented actions and manner-oriented actions. Such a distinction is inspired by the literature pertaining to cognitive linguistics, which indicates that the human conceptual system can distinguish these two distinct types of motion. These two kinds of actions are described in language by more path-oriented or more manner-oriented utterances. In path-oriented utterances, the source, trajectory, or goal is emphasized, whereas in manner-oriented utterances the medium, velocity, or means of motion are highlighted. We examined a video corpus of adult-child interactions comprised of three age groups of children-pre-lexical, early lexical, and lexical-and two different tasks, one emphasizing manner more strongly and one emphasizing path more strongly. We analyzed the language and motion of the caregiver and the gazing behavior of the child to highlight the differences between the tutoring and the acquisition of the manner and path concepts. The results suggest that age is an important factor in the development of these action categories. The analysis of this corpus has also been exploited to develop an intelligent robotic behavior -the tutoring spotter system-able to emulate children's behaviors in a tutoring situation, with the aim of evoking in human subjects a natural and effective behavior in teaching to a robot. The findings related to the development of manner and path concepts have been used to implement new effective feedback strategies in the tutoring spotter system, which should provide improvements in human-robot interaction.
Keywords: Imitation; Tutoring; Adult-child interaction; Human-robot interaction; Semantics; Teachable robots

Robots show us how to teach them: Feedback from robots shapes tutoring behavior during action learning - Vollmer, Anna-Lisa; Mühlig, Manuel; Steil, Jochen J.; Pitsch, Karola; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (PLoS ONE)
Robot learning by imitation requires the detection of a tutor's action demonstration and its relevant parts. Current approaches implicitly assume a unidirectional transfer of knowledge from tutor to learner. The presented work challenges this predominant assumption based on an extensive user study with an autonomously interacting robot. We show that by providing feedback, a robot learner influences the human tutor's movement demonstrations in the process of action learning. We argue that the robot's feedback strongly shapes how tutors signal what is relevant to an action and thus advocate a paradigm shift in robot action learning research toward truly interactive systems learning in and benefiting from interaction.

Intermodal synchrony as a form of maternal responsiveness: Association with language development. - Rohlfing, Katharina; Nomikou, Iris (Language, Interaction and Acquisition)